Evaluating the Performance Properties of Asphalt Produced from Bitumen Modified with Thermoplastic Polymer - Akinleye, M. T.; Salami, L. O.; Joseph, O. P.; Rahmon, R. O.; Tolu-Ilori, I.; Ogungbola, O. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Flexible pavements, particularly in urban areas, deteriorate rapidly after construction due to poor workmanship and inadequate drainage facilities. The demand for roads continues to increase. Engineers of the highway system are concentrating on alternative solutions to meet this expanding challenge.  Highway system engineers are currently focused on developing alternative solutions in order to address this growing challenge. To prevent the premature deterioration of the road system, the performance of flexible pavements must be enhanced. The addition of waste polymers to asphalt mixtures is one method that can significantly enhance the quality of the pavements. This study examined the mechanical properties of asphalt produced from waste plastic polymer-modified bitumen. The addition of thermoplastic polymer (0 to 12%) increased the softening point, viscosity, flash and fire points of bitumen, but decreased its penetration and ductility for the production of hot mix asphalt. The Marshall stability and flow of all asphalt concrete formulations were greater than 9 kN and within 2 - 6 mm of the General Specifications of Nigerian for Road and Bridges, Federal Ministry of Works and Housing, 2016 and the Asphalt Institute, 1991. Modification of asphalt with thermoplastic polymer is suitable for enhancing the performance properties of the asphalt. Additional research is required for the development of recyclable additives that do not significantly increase the final cost of bitumen